2008
DOI: 10.1503/cmaj.070975
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of blood pressure measurement over a sleeved arm versus a bare arm

Abstract: T he measurement of blood pressure is one of the most common examinations undertaken in family practice and has important health and management consequences for the patient. Accurate assessment of blood pressure, therefore, is very important. Current guidelines outline standards for obtaining accurate and reproducible blood pressure measurements.1 These standards include guidelines for the sizes of blood pressure cuffs and the position of the patient's arm, as well as a recommendation that the patient be seate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 10 publications
4
26
0
Order By: Relevance
“…Our results are in line with data in six previous studies [1,[5][6][7][8][9] as shown in Table 4. As there were slight differences in the protocols used in these studies, we present the relevant differences for comparison in Table 4.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with data in six previous studies [1,[5][6][7][8][9] as shown in Table 4. As there were slight differences in the protocols used in these studies, we present the relevant differences for comparison in Table 4.…”
Section: Discussionsupporting
confidence: 93%
“…In clinical practice, these recommendations on removal of clothing are often not followed, and for practical or comfort reasons, clothing is left underneath the cuff. There are some studies that support this practice [1,[5][6][7][8][9], but these have some flaws. Previous studies had the limitations of very few BP readings, use of only one standard cuff bladder size, and absence of randomization.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there were no significant differences between the two different settings. Ma et al14) reported that sleeve thickness had no correlation with the difference between bare- and sleeved-arm readings. In this study, we did not restrict the clothes the patients wore when visiting Gangneung Asan Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This is because we attempted to minimize measurement errors because we had to measure blood pressure a total of six times in each patient. Kahan et al12) and Ma et al14) measured blood pressure using a commercially automatic oscillometric device. There was also a report that oscillometric blood pressure measurements showed no difference from a classic mercury sphygmomanometer 13).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hypertension may be caused by renal disease, oral contraceptives, chronic nonsteroidal anti-inflammatory drugs, antidepressants, pheochromocytoma, primary hyperaldosteronism, renovascular disease, Cushing syndrome, thyroid disease, or sleep apnea (Domino & Kaplan, 2009). Proper measurement is essential and no difference has been noted if a bare arm or sleeved arm is used (Ma, Sabin, & Dawes, 2008). History and physical, electrocardiogram, complete blood count, urinalysis, routine chemistries (glucose, creatinine, electrolytes), total LDL and HDL cholesterol, triglycerides, and estimation of glomerular filtration rate should be conducted (NHLBI, 2010b).…”
Section: Hypertensionmentioning
confidence: 99%